"This Is What Was Birthed": Motherhood and Postfeminist Self-Branding in Tyra Banks' Brand. (July 2015) - Persis Murray, Dara
This article examines the brand development of supermodel cum media mogul Tyra Banks by investigating her positioning as a mother figure in two texts— America's Next Top Model and typeF.com—to facilitate women's postfeminist self-branding as fierce . Grounded in the appropriation of her raced position and the ball culture of the lesbian, gay, bisexual, transgender, and queer community, Banks' mother figure advocates becoming fierce as essential to women's personal and professional success. Fierce signifies hegemonic femininity and postfeminist values, and, accordingly, women under Banks' tutelage engage in immaterial/affective labor on their bodies and emotions to access a positive sense of self and career promise. In doing so, they support fierce as a postfeminist self-brand that provides value for Banks' brand. This study details how motherhood has been drawn on for corporate benefit, encouraging emotional connections between women, texts, and brands that normalize postfeminist self-branding as a means of self-empowerment in early 21st-century consumer culture.